THE ECO-TRADE PARADOX: BALANCING ENVIRONMENTAL PROTECTION AND INTERNATIONAL COMMERCE - Qadir Ullah; Muhammad Jan; Imran Khan; Maseeh Ullah (International Journal of Contemporary Issues in Social Sciences, 2023)
This research article delves into the intricate relationship between environmental protection and international commerce, unveiling the complexities and challenges associated with achieving a harmonious balance. The Eco-Trade Paradox revolves around the inherent tension between the pursuit of economic growth through global trade and the imperative to safeguard the environment. This article critically analyzes the existing legal frameworks, international agreements, and emerging trends that shape the interaction between environmental concerns and the dynamics of international trade. It also proposes innovative approaches to reconcile the seemingly conflicting goals of fostering economic development and preserving the planet’s ecological integrity